2021
DOI: 10.1142/9789811216602_0030
|View full text |Cite
|
Sign up to set email alerts
|

The Southern China Monsoon Rainfall Experiment (SCMREX)

Abstract: A unique program is developed for improving heavy rainfall forecasts over southern China during the presummer rainy season through field campaigns and research on physical mechanisms and convection-permitting modeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 14 publications
1
53
0
Order By: Relevance
“…About a half of the annual rainfall over SC is produced during the pre‐summer rainy season (April to mid‐June) (Luo, 2017). The pre‐summer heavy rainfall over inland SC mainly takes places under influence of fronts, shear lines, vortex, and associated strong low‐level winds to the southeast (Du & Chen, 2018; Huang et al., 2018; M. Li, Luo, Zhang, et al., 2020; Z. Li, Luo, Du, & Chan, 2020; Shen et al., 2020), while the coastal SC features warm‐sector heavy rainfall that is distributed about a few hundred km to the south of a surface front, or in the absence of fronts in SC and the northern SCS (Huang et al., 1986; Luo et al., 2017). The warm‐sector heavy rainfall is mostly produced by mesoscale convective systems (MCSs) (Luo et al., 2013; Xia et al., 2015; Xu et al., 2009) and characterized by abrupt occurrence and strong intensity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…About a half of the annual rainfall over SC is produced during the pre‐summer rainy season (April to mid‐June) (Luo, 2017). The pre‐summer heavy rainfall over inland SC mainly takes places under influence of fronts, shear lines, vortex, and associated strong low‐level winds to the southeast (Du & Chen, 2018; Huang et al., 2018; M. Li, Luo, Zhang, et al., 2020; Z. Li, Luo, Du, & Chan, 2020; Shen et al., 2020), while the coastal SC features warm‐sector heavy rainfall that is distributed about a few hundred km to the south of a surface front, or in the absence of fronts in SC and the northern SCS (Huang et al., 1986; Luo et al., 2017). The warm‐sector heavy rainfall is mostly produced by mesoscale convective systems (MCSs) (Luo et al., 2013; Xia et al., 2015; Xu et al., 2009) and characterized by abrupt occurrence and strong intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence of CI usually depends on multi‐scale atmospheric processes (Rotunno & Houze, 2007; Trier, 2003; Weckwerth & Parsons, 2006). Numerous studies have revealed various factors contributing to CI in the warm‐sector heavy rainfall events over inland and coastal SC, including terrain effects (Du, Chen, Han, Bai, & Li, 2020; Wang et al., 2014), mesoscale cold pools (Liu et al., 2018; Wu & Luo, 2016), surface heating (Jiang et al., 2017), boundary layer (BL) flows of tropical origins (Luo et al., 2017), land‐sea breeze fronts (X. Chen et al., 2017), low‐level jets (LLJs) (Du & Chen, 2018, 2019), and urban heat island effects interacting with onshore BL airflows (Wu et al., 2019; Yin et al., 2020). Previous studies utilizing integrated observations demonstrated the importance of coastline, coastal terrain, upstream oceanic airflow in the BL, and precipitation‐generated cold outflows/pools in triggering and maintaining the extreme rain‐producing MCSs near the SC coasts (Du, Chen, Han, Mai, et al., 2020; Du, Chen, Han, Bai, & Li, 2020; Liu et al., 2018; Wang et al., 2014; Wu & Luo, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luo et al. (2017) and Zheng et al. (2017) showed that there are three strong rainy centers in Guangdong Province, which are located in the eastern coastal belt zone, the west of the Pearl River Delta, and the Beijiang River Valley‐Pearl River Delta block zone, respectively.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Coastal South China (CSC, Figure 1a) is a key region where the East Asian summer monsoon penetrates northward and affects other regions of East Asia (Luo et al., 2017). Due to complex coastal topography and diverse low‐level winds, the DCR in CSC is more complicated than that of inland region.…”
Section: Introductionmentioning
confidence: 99%